Development of molecular tools to monitor conjugative transfer in rhizobia - Torres Tejerizo, Gonzalo Arturo (2015)
Evolution of bacterial populations has been extensively driven by horizontal transfer events. Conjugative plasmid transfer is considered the principal contributor to gene exchange among bacteria. Several conjugative and mobilizable plasmids have been identified in rhizobia, and two major molecular mechanisms that regulate their transfer have been described, under laboratory conditions. The knowledge of rhizobial plasmid transfer regulation in natural environments is very poor. In this work we developed molecular tools to easily monitor the conjugative plasmid transfer in rhizobia by flow cytometry (FC) or microscopy. 24 cassettes were constructed by combining a variety of promotors, fluorescent proteins and antibiotic resistance genes, and used to tag plasmids and chromosome of donor strains. We were able to detect plasmid transfer after conversion of non-fluorescent recipients into fluorescent transconjugants. Flow cytometry (FC) was optimized to count donor, recipient and transconjugant strains to determine conjugative transfer frequencies. Results were similar, when determined either by FC or by viable counts. Our constructions also allowed the visualization of transconjugants in crosses performed on bean roots. The tools presented here may also be used for other purposes, such as analysis of transcriptional fusions or single-cell tagging. Application of the system will allow the survey of how different environmental conditions or other regulators modulate plasmid transfer in rhizobia.